The economic value of seasonal weather and climate services for maize farmers in Manicaland Province of Zimbabwe - Joseph Manzvera; Kwabena Asomanin Anaman; Akwasi Mensah-Bonsu; Alfred Barimah (Heliyon)
Most rural areas in Zimbabwe are extremely vulnerable to changing climatic conditions, particularly droughts, which threaten smallholder farmers' livelihoods. Seasonal weather forecast services can help farmers adapt, optimise production, and implement risk reduction strategies. To support increased investment in these services, this study seeks to provide quantitative evidence on the economic value of locality-specific seasonal weather forecasts by eliciting maize producers' willingness to pay (WTP) through the contingent valuation approach. The results of the study show that among 502 farmers, 68 % would pay for seasonal weather forecasts, highlighting their perceived economic value and practical utility in agricultural decision-making. On average, farmers were willing to pay one (1) United States dollar (US$1) per month for seasonal weather forecast services. Extrapolating this demand nationally, we estimate an annual economic value of around US$ 53.2 million for these services. This valuation underscores the substantial economic benefits that weather and climate services could offer to Zimbabwe's agriculture sector, justifying the case for increased resource allocation towards the delivery of location-specific weather forecasts. Using the Heckman selection model, the study further identified that maize producers' climate change perceptions, radio ownership, and prior participation in agricultural policy development significantly increased their likelihood of paying for seasonal weather forecasts. These factors highlight the role of both access to information and engagement in policy processes in shaping farmers' valuation of seasonal weather forecasts. Establishing district-level climate change dialogue platforms can significantly enhance maize producers' awareness of climate change, deepen their understanding of the value of weather forecasts, and encourage their participation in policy-making processes. By creating spaces for knowledge exchange and farmer engagement, these platforms not only support informed farm decision-making but also help tailor climate services to farmers' needs. Nevertheless, farmers from the Ndau ethnic group and those in remote areas showed reluctance to pay for seasonal weather forecasts, indicating that factors like ethnicity and remoteness affect WTP. This reluctance highlights how social marginalisation and inadequate infrastructure in remote areas limit access to weather information, thereby reducing farmers' perceived value of these services. Enhanced telecommunication infrastructure and radio signals in rural areas, especially community radios, could help to expand the access and tailoring of forecast messages in local languages, making it understandable and thus supporting informed decision-making across diverse farming communities.